Analisis Penggunaan Dana Desa di Kabupaten Konawe Provinsi Sulawesi Tenggara - Taufik, Yani; Rosmawati, Rosmawati; Zani, Munirwan (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2020)
This was a three-month study, undertaken to explore how a village, specifically the village of Tapulaga, allocated funds given by the national government for community empowerment projects. Tapulaga is one of the Soropia villages in Konawe Regency, in Southeast Sulawesi, Indonesia. Analysis of the use of the Village Fund was carried out during the period 2017-2018. Data and information collected in this study were conducted by interviewing key informants (snowball random sampling). Key informants who were considered to have information on the procedures, processes, and use of village funds transferred to the Village Cash Account from the District Cash Account. The first key informant was determined by the village head, further information came from the Village Consultative Body (BPD), the Village Community Empowerment Institute (LPM), community leaders and the Tapulaga Village community. The results showed that during the period 2017-2018 the Village Fund in Tapulaga Village was mostly used only to build a pier; very little allocation was used for community empowerment programs. Although the construction of the pier is closely related to the livelihoods of the local population who are mostly fishermen. It appears that the complexity of the planning and the high cost have resulted in construction which does not function as envisaged. The disbursement of government funding should simply be overseen by the sub-district government, or at least there should have been some checks and balances so the money would not have been wasted.